The effects of size and property type on risk of Malaysian real estate investment trusts (reits) - Lim, Hui Jing, 1987-; Hishamuddin Mohd Ali, supervisor; Fakulti Geoinformasi dan Harta Tanah (2011)
Project Paper (Sarjana Muda Sains (Pengurusan Harta Tanah)) - Universiti Teknologi Malaysia, 2011